Perioperative infections as a prognostic risk factor in hepatocellular carcinoma and cholangiocellular carcinoma: a comparative analysis - Markus S. Jördens; Hannah C. Oswald; Lisa Heinrichs; Nathalie Gassmann; Linda Wittig; Tom Luedde; Sven H. Loosen; Christoph Roderburg; Wolfram T. Knoefel; Georg Fluegen (World Journal of Surgical Oncology)
Abstract Background Hepatocellular Carcinoma (HCC) and cholangiocellular adenocarcinoma (CCA) are the most common primary liver tumors representing a major global health burden. In early disease stages, tumor resection may provide long-term survival in selected patients. However, morbidity and mortality rates are still relatively high after extended liver surgery with perioperative bacterial infections representing major complications. In this study, we evaluate the impact of perioperative infection on the postoperative overall survival (OS) of patients undergoing resection of HCC or CCA. Material and methods Two hundred two patients that received liver surgery for HCC (139) or CCA (63) at our tertiary referral center were included between 2008 and 2020. Infection prior or after surgery was assessed using patient documentation and correlated to patients´ survival rates and other clinical characteristics. Results Patients with perioperative infection displayed a significantly impaired OS compared to patients without a documented infection (419 (95% CI: 262–576) days vs. 959 (95% CI: 637–1281) days; log rank X2(1) = 10.28; p < 0.001). Subgroup analysis revealed that this effect was only observed among HCC patients, while the outcome of CCA patients was independent of pre- or postoperative infections. Moreover, non-anatomical resection of liver tumors was beneficial in patients with HCC (1541 (95%CI: 1110–1972) vs. 749 (95%CI: 0–1528) days; log rank X2(1) = 5.387; p = 0.02) but not CCA. Conclusion Perioperative infection is an important prognostic factor after surgery for HCC but not CCA.